Factors Affecting Customer Satisfaction towards Solar Panel - Bhavna Bhavna Prajapati (International Journal of Marketing & Human Resource Research, 2022)
Energy is a vital factor and an inescapable component for economic advancement. It is also substantial for enhancing and sustaining the quality of life. The solar power goods can be a useful choice for energy production as it is effortlessly accessible and is a fresh resource of energy generation. So, to brand solar products an authenticity, it is indispensable that different research expansion is completed to inventively diminish the cost of solar energy products to make it a worthwhile energy opportunity for all. Solar energy has a dazzling capability to be the clean source of energy for the future and to be employed by individual consumers in India. The study focuses on various factors affecting the satisfaction of the solar panel users. A total of 216 self-administered questionnaire were filled from the respondents through convenience sampling. The factors identified are Environmental concern, Performance and Government initiative. This study will be valuable for marketers and for advertisers to comprehend and reach the target buyers in an efficient way and design marketing plan accordingly.